Detection of Recently Discovered Human Polyomaviruses in a Longitudinal Kidney Transplant Cohort. Issue 9 (19th April 2016) - Bialasiewicz, S.; Rockett, R. J.; Barraclough, K. A.; Leary, D.; Dudley, K. J.; Isbel, N. M.; Sloots, T. P.
Abstract : A large number of human polyomaviruses have been discovered in the last 7 years. However, little is known about the clinical impact on vulnerable immunosuppressed patient populations. Blood, urine, and respiratory swabs collected from a prospective, longitudinal adult kidney transplant cohort (n = 167) generally pre‐operatively, at day 4, months 1, 3, and 6 posttransplant, and at BK viremic episodes within the first year were screened for 12 human polyomaviruses using real‐time polymerase chain reaction. Newly discovered polyomaviruses were most commonly detected in the respiratory tract, with persistent shedding seen for up to 6 months posttransplant. Merkel cell polyomavirus was the most common detection, but was not associated with clinical symptoms or subsequent development of skin cancer or other skin abnormalities. In contrast, KI polyomavirus was associated with respiratory disease in a subset of patients. Human polyomavirus 9, Malawi polyomavirus, and human polyomavirus 12 were not detected in any patient samples. Abstract : Newly discovered human polyomaviruses are uncommonly found in kidney transplant recipients up to one year posttransplant, but in some instances they may be associated with respiratory disease.